2019
DOI: 10.1007/s00382-019-05067-7
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling and quantifying contributions of distinct forcing factors to the observed global sea level pressure field

Abstract: Variations of the global sea level pressure (SLP) field reflect atmospheric and oceanic influences and have a profound influence on temperature, precipitation and the global carbon cycle. The impact of various forcing factors on this field was investigated mainly based on numerical simulations. Alternatively, here we identify and quantify the influences of various forcing factors on observational, reanalysis and simulated SLP fields. By applying canonical correlation analysis (CCA) on the aforementioned data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 100 publications
(120 reference statements)
0
5
0
Order By: Relevance
“…If one assumes that distinct forcing factors are characterized by different temporal evolutions, then CCA can be used to separate the footprint of forcing factors on a given field. CCA has been previously used to identify and link coupled SST–sea level pressure [ 70 ], coupled SST–global high cloud cover patterns [ 71 , 72 ] or coupled SST–Drought Severity Index [ 73 ] patterns to a specific forcing.…”
Section: Methodsmentioning
confidence: 99%
“…If one assumes that distinct forcing factors are characterized by different temporal evolutions, then CCA can be used to separate the footprint of forcing factors on a given field. CCA has been previously used to identify and link coupled SST–sea level pressure [ 70 ], coupled SST–global high cloud cover patterns [ 71 , 72 ] or coupled SST–Drought Severity Index [ 73 ] patterns to a specific forcing.…”
Section: Methodsmentioning
confidence: 99%
“…The computation of SPEI is based on the probability distribution of the difference between PP and PET (PP-PET), and the data are normalized into a log-logistic probability distribu-tion. The potential evapotranspiration data were computed by employing the Penman-Monteith equation (Vanderlinden et al, 2008). The advantage of using SPEI is that it is standardized on a given period and a predefined distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have suggested that due to global warming the large-scale atmospheric circulation has been altered both regionally and globally (Horton et al, 2015;Vaideanu et al, 2020). Any perturbance in the large-scale atmospheric circulation will also lead to changes in the hydroclimate, due to the fact that the atmospheric circulation plays a crucial role in the global and regional hydroclimatic variability (Ionita et al, 2020;Kingston et al, 2006Kingston et al, , 2015Schubert et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Most authors who have studied the space-time evolution of convection cells call upon the analysis in terms of components of sea-level pressure (SLP). SLP is directly related to climate indices (e.g., [35,57]). Decomposition methods often use "Empirical Orthogonal Functions" (EOF).…”
Section: Introductionmentioning
confidence: 99%